Brief Considerations regarding Computer Search - Camelia Bobasu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Computer search is an evidence procedure that involves interfering with a person’s private life; as a result, it must be disposed of only exceptionally. However, computer search should not be confused with access to a computer system, a process that involves entering a computer system or part of it or a means of storing computer data, either directly or remotely through specialized programs or through a network, in order to identifyexisting evidence or that generated during technical surveillance.